Evaluation Of Different Methods Of Infection And Efficacy Of Fungicides Against Sheath Blight Of Rice (Journal of Plant Disease Sciences, 2020)
Sheath blight of rice caused by Rhizoctonia solani (Kuhn) is a destructive disease cause severe losses in rice productivity and grain quality by infecting and destroying rice sheath and leaves. Considering the economic importance of the crop, mode of infection through seed and soil inoculation and efficacy of fungicides against R. solani evaluated. Results of mode of infection through sick soil method which shows seed rot (43.0%) and seedling infection (57.0%) and the mode of infection through seed inoculation recorded seed rot (62.0%) and seedling infection (38.0%). Among the fungicides tested in vitro, propiconazole 13% + difenoconazole 13.9% SC, propiconazole 25% EC, tebuconazole 50% + trifoxystrobin 25% WG, hexaconazole 5% EC and carbendazim 50% WP completely inhibited the radial growth of R. solani however fungicide azoxystrobin (21.11%) and validamaycin (30.37%) found least effective.
Keywords: Rice; Mode of infection; Efficacy; Fungicides